Caste, class, and social movements - Sharma, K. L. (Kanhaiya Lal), 1941 (Jaipur : Rawat Publications, 1986)
Articles, with reference to India.
Includes bibliographies and index.
Keywords: Social classes -- India; Caste -- India; Social mobility -- India; Peasant uprisings -- India